Orbitrap™ monostage MS versus hybrid linear ion trap MS: application to multi‐allergen screening in wine. (December 2014) - Pilolli, Rosa; De Angelis, Elisabetta; Godula, Michal; Visconti, Angelo; Monaci, Linda
<x xml:space="preserve">Abstract</x> Food allergen research has made giant steps in the last years thanks to the features offered by the latest technology of mass analyzers placed on the market allowing multiplex sensitive detection of proteins. Potentials and features of two mass analyzers namely a linear ion trap capable of performing a data dependent or selected reaction monitoring analysis and an OrbitrapTM stand‐alone MS enabling a broadband fragmentation without mass selection at highest mass resolving power are herein described and applied to the multiplex screening of allergens in a type of wine chosen as a reference matrix. Quantitative and confirmative capabilities of both platforms were assessed on the specific case study, the multiple detection of egg and milk ‐related proteins, typically employed in white wines as fining agents. Commercial bioinformatic tools used for a quick allergen identification will be also discussed. Copyright © 2014 John Wiley & Sons, Ltd.